2019
DOI: 10.1371/journal.pone.0214779
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pattern of antibiotic overuse and misuse in primary healthcare hospitals in the southwest of China

Abstract: Purpose Overuse and misuse of antibiotics are the primary risk factors for antibiotics resistance. Inadequate professional competence of primary care physicians might exacerbate these problems in China. This retrospective study aims to document the clinical pattern of antibiotics use and its overuse and misuse rates in rural primary care institutions and to evaluate the association between antibiotics use and characteristics of physicians and their patients. Methods Med… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
4
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 23 publications
5
64
4
5
Order By: Relevance
“…On the other hand, our study found no independent association of P. aeruginosa infection with frequent exacerbations, contradicting the findings from the previous study [ 11 , 12 , 14 , 15 ]. As oral antibiotics and mucolytic are available in many places in China [ 25 ], bronchiectasis patients often take self-prescribed antibiotics irregularly to suppress the symptoms instead of consulting doctors, which potentially underestimates the exacerbation rates and may be the reason we failedto observe the independent effect of P. aeruginosa on frequent exacerbations. Hospitalizations signify a more severe disease condition, heavier disease burden, and high expenditure, despite different admission criteria in different areas.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our study found no independent association of P. aeruginosa infection with frequent exacerbations, contradicting the findings from the previous study [ 11 , 12 , 14 , 15 ]. As oral antibiotics and mucolytic are available in many places in China [ 25 ], bronchiectasis patients often take self-prescribed antibiotics irregularly to suppress the symptoms instead of consulting doctors, which potentially underestimates the exacerbation rates and may be the reason we failedto observe the independent effect of P. aeruginosa on frequent exacerbations. Hospitalizations signify a more severe disease condition, heavier disease burden, and high expenditure, despite different admission criteria in different areas.…”
Section: Discussionmentioning
confidence: 99%
“…In order to speed up the process of informatization, nursing managers should fully realize the importance of information literacy in clinical nursing work [37,38]. Primary hospitals in China are mainly located in township hospitals and community health service stations, with low information level and lagging medical development [39,40]. The score of information literacy of primary nurses in these hospitals was far lower than that of the secondary and tertiary hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Of these two variables, one (sore throat) was not associated with bacteria detection and the other (days since onset of infection) showed an inverse correlation. These differences suggest that the doctors' decision on antibiotics use were not driven mainly by considerations for controlling bacteria pathogens but for assuring the patients or relieving their sense of urgency [28] . Sore throat develops rapidly after onset of infection and is one of the most unpleasant symptoms of RTIs.…”
Section: Determinants Of Antibiotics Use and Bacteria Identi Cationmentioning
confidence: 99%